Case Study Of Surgical Gloves In Malaysia - Seng, Ng Lai (2009)
This paper traces the history of Innovative Polymer, examines the internal and external environments in which it operates, evaluating its strength, weaknesses, opportunities and treats and finally formulating strategies to be employed to repositioned itself in the surgical gloves industry in order to achieve sustainable business growth and profitability.